EP767 A survey of germline mutations with epithelial ovarian cancer in Japanese patients. (1st November 2019) - Abe, A; Mineda, A; Kagawa, T; Kuwahara, A; Nishimura, M
Abstract : Introduction/Background: In Japan, the number of BRCA testing is increasing annually. But, till recently, genetic counselling for epithelial ovarian cancer (EOC) has not been generalized. We investigated the awareness survey and the rate of HRD mutation included gBRCA1/2 mutation with EOC, regardless of their family histories. Methodology: 127 EOC who had treated at our hospital were enrolled. After genetic counselling, DNA was extracted from whole blood, and all coding exons and their flanking intron regions of 11 genes included BRCA1/2, RAD51C/D, ATM, PALB2 and CHEK2 were sequenced with next-generation sequencing in our laboratory. Results: 127 EOC patients who had treated at our hospital were enrolled. After genetic counselling, DNA was extracted from whole blood, and all coding exons and their flanking intron regions of 11 genes included BRCA1/2, RAD51C/D, ATM, PALB2 and CHEK2 were sequenced with next-generation sequencing in our laboratory.In 121 of 125 patients, consent was obtained, of which 84% wanted to disclose results. Mutations were found in 19 (15.7%);7 in gBRCA1 mutation, 10 in gBRCA2 mutation, 1 in gRAD51C mutation, and one in VUS. 12 of pathogenic mutation were high grade serous carcinoma, two; adenocarcinoma, and 4;others.Median age at diagnosis was gBRCA1; 64 years (49–87 years), gBRCA2; 60 years (42–67 years). TC therapy was administered to 10 cases as the first treatment in 19 cases, and all cases PR - CR were obtained. There was no significant difference in OS and PFS with FIGO stage lll of gBRCA mutation (p=0.3, p=0.52) Conclusion: Almost patients with EOC wanted to know genetic risk after genetic counselling. The rate of gBRCA1/2 mutation in tested Japanese EOC patients with an inherited risk, regardless of a family history, was 15.7%. This finding indicates that the cooperation of genetic counselling with other department would be important for patients with ovarian cancers. Disclosure: Nothing to disclose.